Staphylococcus petrasii sp. nov. including S. petrasii subsp. petrasii subsp. nov. and S. petrasii subsp. croceilyticus subsp. nov., isolated from human clinical specimens and human ear infections - Pantůček, Roman; Švec, Pavel; Dajcs, Joseph J; Machová, Ivana; Černohlávková, Jitka; Šedo, Ondrej; Gelbíčová, Tereza; Mašlaňová, Ivana; Doškař, Jiří; Zdráhal, Zbyněk; Růžičková, Vladislava; Sedláček, Ivo (Systematic and applied microbiology, 2013)
Thirteen coagulase-negative, oxidase-negative, and novobiocin-susceptible staphylococci were isolated from human clinical specimens. The isolates were differentiated from known staphylococcal species on the basis of 16S rRNA, hsp60, rpoB, dnaJ, tuf, and gap gene sequencing, automated ribotyping, (GTG)5-PCR fingerprinting, and MALDI-TOF MS analysis. Phylogenetic analysis based on the 16S rRNA gene sequence indicated phylogenetic relatedness of the analyzed strains to Staphylococcus haemolyticus, Staphylococcus hominis, Staphylococcus devriesei, and Staphylococcus lugdunensis. DNA-DNA hybridization experiments between representative strains CCM 8418(T), CCM 8421(T), and the closest phylogenetic neighbors confirmed that the isolates represent novel Staphylococcus species, for which the name Staphylococcus petrasii sp. nov. is proposed. Genotypic and phenotypic analyses unambiguously split the strains into two closely related subclusters. Based on the results, two novel subspecies S. petrasii subsp. petrasii subsp. nov. and S. petrasii subsp. croceilyticus subsp. nov. are proposed, with type strains CCM 8418(T) (=CCUG 62727(T)) and CCM 8421(T) (=CCUG 62728(T)), respectively.
Keywords: stafylokokové infekce; Cluster Analysis; Oxidoreductases; Bacterial Proteins; ucho; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Phylogeny; antibakteriální látky; ribozomální DNA; sekvenční analýza DNA; molekulární sekvence - údaje; shluková analýza; koagulasa; hybridizace nukleových kyselin; oxidoreduktasy; Staphylococcus; Novobiocin; Coagulase; DNA, Bacterial; DNA bakterií; Ear; lidé; novobiocin; Anti-Bacterial Agents; Humans; bakteriální proteiny; Staphylococcal Infections; RNA ribozomální 16S; Bacterial Typing Techniques; Molecular Sequence Data; DNA, Ribosomal; Nucleic Acid Hybridization